2017
DOI: 10.1089/jpm.2017.0340
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Palliative and Hospice Care in the Context of Islam: Dying with Faith and Family

Abstract: A true opportunity to make a lasting impact at the patient level exists for palliative and hospice care researchers if we seek to understand, gain knowledge, and respect Muslim culture and Islamic issues at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…All participants to this study shared the view that people who either face their own death or are experiencing the imminent death of a loved one are often drawn to spirituality and religion as coping strategies. This finding is not surprising or new; previous studies have shown similar or the same results [31,32] but not always drawing from palliative care professionals and in a period politically and religiously charged in the UK [33].…”
Section: Resultssupporting
confidence: 65%
“…All participants to this study shared the view that people who either face their own death or are experiencing the imminent death of a loved one are often drawn to spirituality and religion as coping strategies. This finding is not surprising or new; previous studies have shown similar or the same results [31,32] but not always drawing from palliative care professionals and in a period politically and religiously charged in the UK [33].…”
Section: Resultssupporting
confidence: 65%
“…13,40 The existing literature has explored the barriers to its use in Muslim communities. 4 However, many of these philosophical concerns are less prominent in our findings, perhaps due to the absence of strong opioids and only limited availability of weak opioids in rural settings. In our sample, community leaders, including imams, emphasise the health professionals’ obligation to employ all available methods to relieve suffering.…”
Section: Discussionmentioning
confidence: 69%
“…3 Research has documented how Islamic beliefs and practices pertain to palliative care issues. 47 However, such generalisations of a universal image of Islam can lead to stereotyping and prejudice. 8,9 Islam does have much which unites its global adherents; however, there are ethnic, cultural and social differences in beliefs and practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the difference did not reach the level of significance, a trend towards a lower frequency of choices for hospices by families of Turkish origin was found. End-of-life care in hospices may not exactly match preferences of Turkish or Muslim families who in turn may benefit from a stronger family support [ 18 ].…”
Section: Discussionmentioning
confidence: 99%